Olfactory outcomes in the management of aspirin exacerbated respiratory disease related chronic rhinosinusitis. Issue 4 (1st December 2020) - Spielman, Daniel B.; Overdevest, Jonathan; Gudis, David A.
Abstract : Patients with aspirin exacerbated respiratory disease (AERD) experience a severe and recalcitrant form of chronic rhinosinusitis with nasal polyposis (CRSwNP) and asthma, which are exacerbated by aspirin/NSAID ingestion. As compared with aspirin‐tolerant CRSwNP, patients with AERD experience more severe olfactory dysfunction, which is one of the key contributors to the observed decrease in quality of life (QOL) in this disease. The objective of this paper is to review the published olfactory outcomes observed with various treatment modalities.